Rbp95 binds to 25S rRNA helix H95 and cooperates with the Npa1 complex during early pre-60S particle maturation. Issue 17 (26th August 2022) - Bhutada, Priya; Favre, Sébastien; Jaafar, Mariam; Hafner, Jutta; Liesinger, Laura; Unterweger, Stefan; Bischof, Karin; Darnhofer, Barbara; Siva Sankar, Devanarayanan; Rechberger, Gerald; Abou Merhi, Raghida; Lebaron, Simon; et al.
Abstract: Eukaryotic ribosome synthesis involves more than 200 assembly factors, which promote ribosomal RNA (rRNA) processing, modification and folding, and assembly of ribosomal proteins. The formation and maturation of the earliest pre-60S particles requires structural remodeling by the Npa1 complex, but is otherwise still poorly understood. Here, we introduce Rbp95 (Ycr016w), a constituent of early pre-60S particles, as a novel ribosome assembly factor. We show that Rbp95 is both genetically and physically linked to most Npa1 complex members and to ribosomal protein Rpl3. We demonstrate that Rbp95 is an RNA-binding protein containing two independent RNA-interacting domains. In vivo, Rbp95 associates with helix H95 in the 3′ region of the 25S rRNA, in close proximity to the binding sites of Npa1 and Rpl3. Additionally, Rbp95 interacts with several snoRNAs. The absence of Rbp95 results in alterations in the protein composition of early pre-60S particles. Moreover, combined mutation of Rbp95 and Npa1 complex members leads to a delay in the maturation of early pre-60S particles. We propose that Rbp95 acts together with the Npa1 complex during early pre-60S maturation, potentially by promoting pre-rRNA folding events within pre-60S particles.